Multi-Layer Controls of Cas9 Activity Coupled With ATP Synthase Over-Expression for Efficient Genome Editing in Streptomyces - Wang, Kai; Zhao, Qing-Wei; Liu, Yi-Fan; Sun, Chen-Fan; Chen, Xin-Ai; Burchmore, Richard; Burgess, Karl; Li, Yong-Quan; Mao, Xu-Ming (Frontiers in Bioengineering and Biotechnology, 2019)
Efficient genome editing is a prerequisite of genetic engineering in synthetic biology, which has been recently achieved by the powerful CRISPR/Cas9 system. However, the toxicity of Cas9, due to its abundant intracellular expression, has impeded its extensive applications. Here we constructed a genetic cassette with triple controls of Cas9 activities at transcriptional, translational and protein levels, together with over-expression of the ATP synthase -subunit AtpD, for the efficient genome editing in Streptomyces. By deletion of actII-ORF4 in Streptomyces coelicolor as a model, we found that constitutive expression of cas9 had about 90% editing efficiency but dramatically reduced transformation efficiency by 900-fold. However, triple controls of Cas9 under non-induction conditions to reduce its activity increased transformation efficiency over 250-fold, and had about 10% editing efficiency if combined with atpD overexpression. Overall, our strategy accounts for about 30-fold increased possibility for successful genome editing under the non-induction condition. In addition, about 80% editing efficiency was observed at the actII-ORF4 locus after simultaneous induction with thiostrepton, theophylline and blue light for Cas9 activity reconstitution. This improved straightforward efficient genome editing was also confirmed in another locus redD. Thus we developed a new strategy for efficient genome editing, and it could be readily and widely adaptable to other Streptomyces species to improve genetic manipulation for rapid strain engineering in Streptomyces synthetic biology, due to the highly conserved genetic cassettes in this genus.